PENGARUH PENGEMBANGAN SDM, MANAJEMEN TALENTA DAN MANAJEMEN PENGETAHUAN TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN BIDANG LAYANAN DAN BIDANG PEMASARAN BANK DKI KCU BALAIKOTA) - Wiwin Finta Utami; Deni Wardani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2021)
The rapid competition of the banking business requires the company to improve the quality of service by improving employee performance. Therefore, companies need to pay attention to factors that can affect employee performance. The main factors that can affect employee performance are continuous development and improvement of individual factors including talent and knowledge. This research aims to test the influence of human resources development, talent management and knowledge management on the performance of permanent employees working in the field of services and marketing at Bank DKI KCU Balaikota with a sample number of 50 respondents. The sampling techniques in this study used saturated samples and data processing using SPSS 21. The results of this study show that human resources development variables partially affect the performance of employees of Bank DKI KCU Balaikota. Talent management variables have no effect on the performance of Bank DKI KCU Balaikota employees and knowledge management variables also partially have no effect on the performance of employees of Bank DKI KCU Balaikota.